IDENTIFYING BEST PRACTICES FOR REDUCING SOCIAL ISOLATION AMONG COMMUNITY-DWELLING OLDER ADULTS. (11th November 2018) - Gruenewald, T L; Batra, R; Meyer, M; Likar, D
Abstract: Loneliness and social isolation are significant public health issues, affecting over one third of adults age 45 and older. Both are predictive of cognitive and physical functioning, morbidity, and mortality. Despite significant prevalence of these conditions and their import for health, few effective and widely-used programs exist to enhance social connections and decrease loneliness. In an effort to build an intervention that could be delivered to community-dwelling older adults, we conducted a critical review of the experimental and quasi-experimental intervention literature aimed at reducing feelings of loneliness or social isolation in older adults. Our goals were to identify intervention elements shown to be most effective in reducing these outcomes and identify the most sensitive assessment tools for these conditions. Our presentation will provide an overview of how this knowledge was translated into a home-based community intervention and share findings from initial implementation of the program.